Percutaneous ultrasound-guided medication injection: a potential technique for subglottic stenosis - Deng, Mingming; Tong, Run; Lin, Jieru; Bian, Yiding; Zhou, Guowu; Herth, Felix; Hou, Gang (Respiration, 2024)
Introduction: Subglottic stenosis, manifested by granulation tissue hyperplasia, is challenging and requires multiple repeated treatments and stent maintenance at times. Corticosteroids prevent severe subglottic stenosis development owing to their antifibrotic and anti-inflammatory properties. Submucosal injection of glucocorticoids, a useful adjuvant therapeutic method, improves the mean interval between endoscopic procedures and reduces airway restenosis risks. Case Presentation: We report a rare case of a man with complex subglottic stenosis who underwent balloon dilatation combined with cryotherapy, stent placement, and adjuvant submucosal triamcinolone injection. The drug was injected efficiently and safely into the submucosal layer under percutaneous ultrasound guidance, and subglottic stenosis was well-controlled at a low cost. Conclusion: POCUS-guided medication injections may be a useful adjuvant medical therapy for subglottic stenosis.
Veröffentlicht: June 27 2024
Gesehen am 19.02.2025